2020
DOI: 10.3389/fbioe.2020.00166
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Protein Corona of Nanoparticles and in the Formulation of “Stealthy” Nanomaterials

Abstract: In the last decades, the staggering progress in nanotechnology brought around a wide and heterogeneous range of nanoparticle-based platforms for the diagnosis and treatment of many diseases. Most of these systems are designed to be administered intravenously. This administration route allows the nanoparticles (NPs) to widely distribute in the body and reach deep organs without invasive techniques. When these nanovectors encounter the biological environment of systemic circulation, a dynamic interplay occurs be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(186 citation statements)
references
References 88 publications
1
184
1
Order By: Relevance
“…The biocorona can consist of hundreds of proteins, which influence the physical and chemical properties of the nanoparticles, such as, size, morphology, aggregation state, hydrophobicity, and permeability. Hence, it is difficult to predict the behavior of nanoparticles in biological systems [ 13 , 18 , 33 ]. Ho et al studied how biomolecules influenced the stability of gold nanoparticles and showed that serum proteins at high concentrations stabilized the nanoparticles, whereas lower concentrations enhanced nanoparticle aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocorona can consist of hundreds of proteins, which influence the physical and chemical properties of the nanoparticles, such as, size, morphology, aggregation state, hydrophobicity, and permeability. Hence, it is difficult to predict the behavior of nanoparticles in biological systems [ 13 , 18 , 33 ]. Ho et al studied how biomolecules influenced the stability of gold nanoparticles and showed that serum proteins at high concentrations stabilized the nanoparticles, whereas lower concentrations enhanced nanoparticle aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments regarding blood plasma and albumin bring insight to one of the essential nanotechnological tasks, that is, the preliminary autologous biocorona formation at the nanoparticle surface before medical application. Autologous biocorona formation is considered to be very promising for advanced nanovesicle technology for cancer treatment [ 13 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To fully understand the impact of the protein corona and its importance in the targeted therapeutic systems, it is necessary to determine which proteins are adsorbed on the surface of a particle, their kinetics of adsorption, affinity, and stoichiometry of adsorbtion and desorption [ 19 ]. There are several techniques for separating and identifying plasma proteins that are absorbed on the surface of nanoparticles such as centrifugation, gel filtration, magnetic separation [ 20 ].…”
Section: Analytical Methods For Characterizing the Protein Coronamentioning
confidence: 99%
“…The newly formed PC provides NPs a biological identity; they can present a discernible molecular pattern that determines the bioavailability, colloidal stability, biodistribution, cellular uptake, toxicity, and clearance from the body. What makes it more complicated is the process of dynamic PC formation, as it also depends on the competition between proteins adsorbed on the surfaces of NPs [ 60 , 61 , 62 ].…”
Section: Risk Assessment Of Silver Nanoparticles To Soil Invertebrmentioning
confidence: 99%